Implementasi SJPH dan CPPB untuk Peningkatan Daya Saing Usaha Produk “Rempah 77” - Poppy Arsil; Rumpoko Wicaksono; Ardiansyah Ardiansyah (Penerbit Goodwood, 2026)
Purpose: This community service programme aims to empower 'Rempah 77' business group by providing technical guidance on the implementation of the Halal Product Assurance System (HPAS) and Good Manufacturing Practices (GMP). Methodology/approach: The activities consist of technical guidance on the implementation of HPAS and GMP. The HPAS material refers to the Decree of the Head of the Halal Product Assurance Agency Number 20 of 2023 regarding the Criteria for the HPAS, while the GMP material refers to the Regulation of the Head of Indonesian Food and Drug Control Agency Number Hk.03.1.23.04.12.2206 of 2012 on GMP for the Home Industry. Results: The target audience is able to implement the HPAS and GMP. The implementation of HPAS has resulted in the attainment of halal certificate, while the implementation of GMP has resulted in improved facilities and infrastructure to support the processing of healthy and safe products Conclusions: Technical guidance and assistance in the implementation of HPAS and GMP have resulted in the establishment of a halal assurance system in the ‘Rempah 77’ business group and have obtained a halal certificate. Production facilities and infrastructure become more suitable to support the production of ‘Rempah 77’ products that are of high quality and safe for consumption. Limitations: This study focuses solely on small enterprises that produce spice drinks. Contributions: This study outlines the steps that can be adopted by other small beverage enterprises for the implementation of the Halal Assurance System and Good Manufacturing Practices (GMP).